Comparison of physical fitness in elderly submitted to different physical exercise interventions - Campos, Leonardo (2016)
The objective was to investigate the influence of two types of physical exercise intervention on elderly individuals’ physical fitness. The study included 17 older adults with a mean age of 65.8 years (± 2.88), divided into two groups: Programa de Exercícios Físicos em Unidades de Saúde (PEFUS – Physical Exercise Program in Health Units, n = 8) and Adapted Volleyball (n = 9). PEFUS classes were held three times a week and lasted 90 minutes, including strength, aerobic endurance, agility, coordination and balance exercises. Adapted Volleyball classes were performed two times per week and lasted 120 minutes, divided into skill volleyball exercises and game. For the evaluation of physical skills (strength, agility, coordination and flexibility), the American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD) set of tests was performed. All participants were assessed at the baseline and after three months of interventions. Statistical analysis was performed using factorial ANOVA through SPSS, version 17.0, and a significance level p <0.05. Motor coordination showed significant improvements after three months of interventions, decreasing from 11.7 ± 2.3 to 10.1 ± 1.6 seconds for Adapted Volleyball and from 15.8 ± 3.3 to 12.0 ± 3.5 seconds for PEFUS (p <0.05). Regarding strength endurance, there was a group-moment interaction (p <0.05) and the PEFUS group showed an increase in this variable after intervention. The interventions are beneficial to the physical fitness of elderly individuals, because they increase or maintain such fitness after these interventions.